The messenger - Wright, Charles, 1932-2008 (Farrar, Straus & Compnay, 1963)
In The Messenger (1963), Wright draws extensively on his life. Realistically narrated in the first person by Charles Stevenson -- a light-skinned African American newcomer to Manhattan from small-town Missouri -- the novel dramatizes the isolation and alienation of those who fall prey to America's social, economic, and racial caste systems. Stevenson works as an office messenger and constantly finds himself on the edges of power, yet is utterly devoid of any. A man perceived as neither black nor white, "a minority within a minority," he drifts through the naturalistic city of New York, where victory and defeat are accepted "with the same marvelous indifference."